Proses Pembentukan Kata Berafiks dalam Bahasa Indonesia Ragam Sastra Modern - Eka Wahyu Lestari; Agustina (Persona: Kajian Bahasa dan Sastra, 2023)
This research aims to, (1) describe the variety of confixes and combinations of affixes contained in the novel Sesuk by Tere Liye. (2) describe the process of forming and the patterns of confixes and combinations of affixes contained in the novel Sesuk by Tere Liye. This research is a qualitative research with descriptive method. The results found first, it is known that there are four types of confixes namely ke-an, per-an, peN-an, ber-an and seventeen types of affix combinations in the form of meN-kan, meN-i, memper-kan, memper-i, ber-kan, ber-an, kese-an, ter-kan, per-kan, per-an, peN-an, se-nya, di-i, di-i, di-kan, semeN-kan, and combined infix. Second, based on the pattern of formation, 101 patterns of confixes and combinations of affixes with 8 formation functions were found, namely (1) verb-forming confixes, (2) noun-forming confixes, (3) adjective-forming confixes, (4) verb-forming affix combinations, (5) combinations affixes forming nouns, (6) combinations of affixes forming adjectives, (7) combinations of affixes forming adverbs.